Rearch and implementation of constant beamwidth time-demain beamformer based on Farrow structure - Tian ZHOU; Bing-zhi ZHANG; Wei-dong DU; Dong-dong PENG (Tongxin xuebao)
A new constant beamwidth time-domain beamformer based on Farrow structure filter was proposed, which consists of a digital delay unit to achieve time delay of integral times sampling interval, a high-precision fractional delay filter unit implemented by Farrow structure, and an amplitude weighing unit to ensure constant beamwidth. First, princi-ples, features and advantages of the proposed beamformer was analyzed theoretically. Then its validity and superiority was proved via computer simulation. Finally, its good efficiency and practicability in realtime implementation was tested on C6748 DSP.